2015
DOI: 10.1002/hep.27660
|View full text |Cite
|
Sign up to set email alerts
|

Vps4A functions as a tumor suppressor by regulating the secretion and uptake of exosomal microRNAs in human hepatoma cells

Abstract: The deregulation of microRNAs (miRNAs) plays an important role in human hepatocarcinogenesis. In this study, we highlight exosomes as mediators involved in modulating miRNA profiles in hepatocellular carcinoma (HCC) cells. First, we examined the different miRNA expression profiles in HCC cells and HCC cell–derived exosomes. Next, coculture experiments indicated that HCC cell–derived exosomes promoted the cell growth, migration, and invasion of HCC cells and had the ability to shuttle miRNAs to recipient cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
151
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(169 citation statements)
references
References 40 publications
4
151
0
Order By: Relevance
“…In the study done by Kogure et al the transfer of some miRNAs into HepG2 through an uptake of Hep3B-derived exosomes resulted in the suppression of transforming growth factor β activated kinase-1 (TAK1), and this loss of TAK1 activity was believed to be associated with hepatocarcinogenesis (60). In another recent report, exosomes derived from HCC cell line SMMC-7721 cells can in turn promote the growth and proliferation, metastasis, and invasion of the cells themselves (61). In addition, the exosomes released from highly migratable HCC cell lines (HKCI-C3, HKCI-8 and MHCC97L) carry an abundant amount of protumorigenic RNA and proteins, including MET protooncogene, S100 family members (S100A4, S100A10, and S100A11), and caveolins (CAV-1 and CAV-2), which increase the production of active matrix metalloproteinases (MMP)-2 as well as MMP-9 by activating the PI13K/AKT and MAPK signaling pathways, thus significantly enhancing the ability of non-motile hepatocyte cell line to migrate and invade (62).…”
Section: The Role Of Exosomes In Tumorigenesis and The Development Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study done by Kogure et al the transfer of some miRNAs into HepG2 through an uptake of Hep3B-derived exosomes resulted in the suppression of transforming growth factor β activated kinase-1 (TAK1), and this loss of TAK1 activity was believed to be associated with hepatocarcinogenesis (60). In another recent report, exosomes derived from HCC cell line SMMC-7721 cells can in turn promote the growth and proliferation, metastasis, and invasion of the cells themselves (61). In addition, the exosomes released from highly migratable HCC cell lines (HKCI-C3, HKCI-8 and MHCC97L) carry an abundant amount of protumorigenic RNA and proteins, including MET protooncogene, S100 family members (S100A4, S100A10, and S100A11), and caveolins (CAV-1 and CAV-2), which increase the production of active matrix metalloproteinases (MMP)-2 as well as MMP-9 by activating the PI13K/AKT and MAPK signaling pathways, thus significantly enhancing the ability of non-motile hepatocyte cell line to migrate and invade (62).…”
Section: The Role Of Exosomes In Tumorigenesis and The Development Ofmentioning
confidence: 99%
“…Human macrophages can also transmit miRNA to HCC cells to inhibit cell proliferation via exosomes (73). Recent research revealed that exosomes containing Vps4A (a tumor suppressor) can reduce the proliferation, metastasis, and invasion of HCC cells (61). In addition, under stress conditions, tumor cells can release exosomes to adapt themselves to the surrounding environment.…”
Section: Roles Of Exosomes In Hepatic Tumor Growth Suppression and Trmentioning
confidence: 99%
“…Levine and colleagues have shown that the p53 regulated gene TSAP6 increases exosome production in p53 activated cells in response to stress [50]. Taking into account the importance of tumor suppressor genes in exosome production, Wei et al showed that tumor suppressor Vps4A is downregulated in Human Hepatoma Cells (HCC) and it is involved in miR sorting into exosomes [51]. Upon ectopic expression of Vps4A in HCC, it was found that Vps4A enhanced secretion of oncogenic miRs in exosomes and as well accumulation of tumor suppressor miRs in cells.…”
Section: Mir-selective Sorting Mechanisms In Exosomesmentioning
confidence: 99%
“…The underlying cause for enhanced levels of exosome production remains unclear. Cancer cell-derived exosomes function in an autocrine or paracrine manner to modulate the tumour microenvironment [15] . Moreover, the cargo shuttled by tumour-derived exosomes determines their effect on target cells, and the exosomes play important roles in their ability to influence tumour growth and progression.…”
Section: Exosome-based Liquid Biopsymentioning
confidence: 99%
“…For example, Hep3B, HepG2 and PLC/PRF/5 cell-derived exosomes can modulate the expression of transforming growth factor-β activated kinase-1(TAK1) and associated downstream signalling and enhance transformed cell growth in recipient cells [54] . Furthermore, vacuolar protein sortin 4 homolog A (VPS4A) regulates exosomemediated aberrant miRNA expression in HCC cells [15] . The potential of exosomes to transfer lncRNA is increasingly recognised.…”
Section: Intercellular Communicationmentioning
confidence: 99%